Treatment of Hominis placenta pharmacopuncture for a patient with mild neurocognitive disorder: Case report - Yunna Kim; Yoon Ji Eom; Seung-Hun Cho (Korean Pharmacopuncture Institute, 2019)
Hominis placenta pharmacopuncture, a treatment that injects Hominis placenta extract into acupoints, has been suggested in the literature and researches that it could be used for cognitive decline. We experienced a case of mild neurocognitive disorder treated with Hominis placenta pharmacopuncture. Hominis placenta pharmacopuncture could be a possible treatment modality producing substantial clinical result in cognitive function which is assessed with Mini-Mental State Examination-Dementia Screening (MMSE-DS), Korean Version of Montreal Cognitive Assessment (MoCA-K), and Korean-Dementia Rating Scale (K-DRS). A 84-yearold man with mild neurocognitive disorder received Hominis placenta pharmacopuncture on GV20, CV12, and bilateral ST36 for a month. The results of neuropsychological examination showed increase in scores after treatment of Hominis placenta pharmacopuncture. Before treatment, they were 15 points for MoCA-K, and 120 points for K-DRS (7.6%), but after treatment, they elevated by 21 points for MoCA-K and 137 points for K-DRS (100%). MMSE-DS score was 28 points, unchanged before and after treatment. It did not cause any side-effect. Hominis placenta pharmacopuncture could be a safe option for treating mild neurocognitive disorder.